Agglomeration economies and labour markets in Brazil - Barufi, Ana Maria Bonomi (2015)
Agglomeration economies have a relevant impact on local labour markets. The interaction of workers and firms in dense urban areas may generate productivity advantages that result in higher wages. They may be accompanied by an increase in local costs, but the existence of cities that continue to grow is a sign by itself that these gains supersede higher costs. Therefore, large urban areas have an expected positive impact on wages. However, not only the size of the city but also the sectoral composition is relevant to understand locational choices of firms of a specific sector. The industrial scope of agglomeration economies is investigated in the first chapter of this dissertation, and the main results indicate that there is not a unique optimal local industrial mix to foster productivity in different technological sectors. Furthermore, high-tech and low-tech manufacturing sectors benefit more from urban scale in Brazil, followed by services associated with higher knowledge intensity. These sectors are supposed to locate relatively more in large urban areas in order to profit from these advantages. Agglomeration economies may have static and dynamic effects for individuals. These effects are reinforced by a process of sorting of skilled workers into large urban areas. In fact, initial and return migration are mechanisms that select more skilled and more productive workers into large urban areas. Then, cities with a higher percentage of skilled workers attract more of these highly-qualified individuals. Second migration seems to reinforce these relations. The estimation of static agglomeration economies indicate that the inclusion of individual fixed effects decreases density coefficient significantly. Then, dynamic agglomeration economies are estimated considering previous work experience in cities. In this case, static agglomeration advantages become insignificant and whenever years of previous experience are combined with the current place of work, individuals working in less dense cities who had previous experience in denser areas will benefit the most from these gains. Finally, controlling for worker heterogeneity previous experience has a relevant and positive impact on wage growth only in cities with at least the same density level of the current place of work. Finally, city size has an important impact on the relative bargaining power of workers and firms in the labour market. When analysing the relationship of local wages and the business cycle, wage flexibility, measured by the wage curve, is higher in informal sectors in less dense areas. Therefore, large agglomerations are supposed to provide a higher bargaining power for workers, as they have further job opportunities. All these results indicate that agglomeration economies in Brazil are likely to stimulate spatial concentration and increase regional inequalities. Workers and firms self-select themselves into agglomerated urban areas, in which they find a more diversified environment and a larger share of high-skilled individuals. Bigger centres also provide the conditions for workers to bargain for higher wages, even if they are in the informal sector.